2017
DOI: 10.18632/oncotarget.18856
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of systemic immune-inflammation index in solid tumors: a systematic review and meta-analysis

Abstract: BackgroundInflammation may play an important role in cancer progression, and a higher systemic immune-inflammation index (SII) has been reported to be a poor prognostic marker in several malignancies. However, the results of published studies are inconsistent.Materials and MethodsA systematic review of databases was conducted to search for publications regarding the association between blood SII and clinical outcome in solid tumors with a date up to February 12, 2017. The primary outcome was overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
229
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 34 publications
11
229
2
3
Order By: Relevance
“…Recently, SII was developed as a new index based on circulating immune‐inflammatory cells, such as platelets, neutrophils and lymphocytes. The index has been widely reported to be associated with poor outcomes in patients with various cancers, 16‐18 indicating that it could be useful as a biomarker for future outcomes. In our study, the ACS group had higher SII score and WBC values, which reflect more severe inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SII was developed as a new index based on circulating immune‐inflammatory cells, such as platelets, neutrophils and lymphocytes. The index has been widely reported to be associated with poor outcomes in patients with various cancers, 16‐18 indicating that it could be useful as a biomarker for future outcomes. In our study, the ACS group had higher SII score and WBC values, which reflect more severe inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the systemic immune‐inflammation index (SII) was developed based on the platelet counts and NLR (SII, platelets count × neutrophil/lymphocyte ratio) to consider patients’ inflammatory and immune status simultaneously. A high SII was reported to be associated with poor outcomes in cancer patients, 16‐18 which indicates that the index could be used as a marker of prognostic value in various malignant diseases. To our interest, it has been mentioned that SII may also be associated with adverse outcomes in chronic heart failure 19 which suggests potential implications in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…SII is a novel inflammation index, which was defined as follows: Plt × Neu / lymphocyte count . Recently, SII has been investigated as a prognostic marker in various malignancies, and it was reported as a more objective factor that represents the balance between the inflammatory and immune response of hosts compared with NLR and PLR . Lolli et al .…”
Section: Parameters Associated With Inflammationmentioning
confidence: 99%
“…75 SII is a novel inflammation index, which was defined as follows: Plt 9 Neu / lymphocyte count. 76 Recently, SII has been investigated as a prognostic marker in various malignancies, and it was reported as a more objective factor that represents the balance between the inflammatory and immune response of hosts compared with NLR and PLR. 76 Lolli et al showed that pretreatment SII and its changes at 6 weeks after starting systemic therapy are independent predictive and prognostic factors for patients with mRCC who underwent sunitinib treatment, and that the improvement of SII at 6 weeks was associated with a better prognosis.…”
Section: Inflammatory Indexes Consisting Of Peripheral Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation